Influence of Escherichia coli lipopolysaccharide induced fever on the plasma kinetics of cefquinome in buffalo calves - MANGAL, MUKESH; SHARMA, K (The Indian Journal of Animal Sciences, 2015)
The pharmacokinetic behavior of cefquinome was studied in healthy and febrile buffalo calves after single intramuscular administration (2 mg/kg). The fever was induced with Escherichia coli lipopolysaccharide (1 μg/kg, IV). The drug concentration in plasma was detected by HPLC method. Pharmacokinetic analysis of disposition data indicated that intramuscular administration data were best described by one-compartment open model. At 2.5 min, concentrations of cefquinome in healthy and febrile animals were 2.21±0.38 and 2.52±0.38 μg/ml, respectively, and drug was detected up to 24 h. The peak plasma levels of cefquinome in febrile buffalo calves (7.70±0.46μg.ml-1) and healthy buffalo calves (6.70±0.46μg.ml-1) were achieved at 45 min and 30 min, respectively. The absorption half life (t1/2ka) of cefquinome was similar in healthy and febrile buffalo calves. Drug distribution was altered by fever as febrile animals showed volume of distribution (0.37±0.07L/kg) lower than healthy animal (0.69±0.04 L/ kg). Total body clearances in healthy and febrile animals were 0.09 and 0.04 L/kg/h, respectively. To maintain minimum therapeutic concentration of 0.1 mg/ml, a satisfactory dosage regimen of cefquinome in healthy and febrile buffalo calves would be 2.8 mg/kg and 1.2 mg/kg body weight, respectively, to be repeated at 24 h intervals.